Effectiveness of Systematic Health Education Model for Type 2 Diabetes Patients - Yongwen Zhang; Lanfang Chu (International Journal of Endocrinology)
Background. Health education is considered to be essential in the overall care of patients with type 2 diabetes mellitus (T2DM); systematic health education integrates individual education not only during hospitalization but also extended care outside of a hospital. To test effectiveness of the systematic health education model for T2DM, we conducted a randomized study with a control group among patients with T2DM living in Nanjing, China. Methods. 998 eligible patients completed the enrollment and were randomized to systematic health education model and conventional model groups (498 and 500 patients, resp.). The systematic health education model was based on the following aspects: image education, visitation of the exhibition hall, dissemination of educational materials, individualized medical nutrition therapy and exercise programs, WeChat group and regular health lectures, evaluation of complications, lifestyle modification, systematic treatment scheme, self-monitoring of glycemic control, monthly evaluation of the therapeutic effect, proposed improvement measures, and individualized follow-up scheme. The main outcome measures were glycated hemoglobin A1c (HbA1c), blood pressure, body mass index (BMI), and lipids during the 2-year follow-up. Results. The systematic health education model led to a favorable variation in HbA1c, LDL cholesterol, and systolic blood pressure (SBP) (P<0.05). After adjusted analysis, the HbA1c decreased by 0.67% (P<0.01) in the systematic health education model, SBP decreased by 10.83 mmHg (P<0.01), and the level of diastolic blood pressure (DBP), HDL cholesterol, and total cholesterol decreased slightly and was not significant. The BMI did not change significantly during the study in either of the two groups. Conclusions. The systematic health education model is a useful method in the treatment of T2DM because it contributes to decrease in HbA1c, LDL cholesterol, and SBP levels, as well as helps in increasing the compliance with the control criteria, except for DBP and BMI.